2005
DOI: 10.1603/0022-0493-98.2.389
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Three Resistance Sources in Winter Wheat Derived from TAM 107 on Yield Response to Russian Wheat Aphid

Abstract: A study to determine yield response to the Russian wheat aphid, Diuraphis noxia (Mordvilko), was conducted during the 1997-1998 and 1998-1999 growing seasons at three eastern Colorado locations, Akron, Fort Collins, and Lamar, with three wheat lines containing either Russian wheat aphid-resistant Dn4 gene, Dn6 gene, or resistance derived from PI 222668, and TAM 107 as the susceptible control. Russian wheat aphids per tiller were greater on TAM 107 than the resistant wheat lines at the 10x infestation level at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Management of D. noxia has largely relied on resistant wheat cultivars (Smith 1999, Webster andKenkel 1999). Wheat cultivars containing D. noxia-resistant genes, which have different levels of antibiosis, tolerance, or both (Randolph et al 2005a), have been shown to harbor fewer D. noxia populations and have higher yields compared with their susceptible wheat counterparts (Randolph et al 2003(Randolph et al , 2005b. Resistant plants also have demonstrated compatibility with other management tactics by exhibiting an absence of leaf rolling when infested with D. noxia, which would expose the aphids to chemical and biological management (Hawley et al 2003).…”
mentioning
confidence: 99%
“…Management of D. noxia has largely relied on resistant wheat cultivars (Smith 1999, Webster andKenkel 1999). Wheat cultivars containing D. noxia-resistant genes, which have different levels of antibiosis, tolerance, or both (Randolph et al 2005a), have been shown to harbor fewer D. noxia populations and have higher yields compared with their susceptible wheat counterparts (Randolph et al 2003(Randolph et al , 2005b. Resistant plants also have demonstrated compatibility with other management tactics by exhibiting an absence of leaf rolling when infested with D. noxia, which would expose the aphids to chemical and biological management (Hawley et al 2003).…”
mentioning
confidence: 99%
“…Mornhinweg et al [9] found that the effect of RWA feeding on grain yield and yield components varied with RWA resistance, where resistant lines showed increased grain yield. Randolph et al [10] concluded that resistant wheat lines could yield more than susceptible wheat lines in the presence of Russian wheat aphid. Current management practices for winter wheat include the use of resistant cultivars, and it is important to ensure that cultivars released in South Africa have sufficient, but more importantly, lasting resistance against the Russian wheat aphid in order to minimize yield losses as far as possible.…”
Section: Introductionmentioning
confidence: 99%